Optimization design of tetra-primer ARMS-PCR using SNP lectin gene and in silico characterization of lectin protein in rodent tuber (Typhonium flagelliforme) mutant of Bogor accessions - NESTI F. SIANIPAR; ZIDNI MUFLIKHATI; KHOIRUNNISA ASSIDQI (Smujo International, 2024)
Abstract. Sianipar NF, Muflikhati Z, Assidqi K. 2024. Optimization design of tetra-primer ARMS-PCR using SNP lectin gene and in silico characterization of lectin protein in rodent tuber (Typhonium flagelliforme) mutant of Bogor accessions. Nusantara Bioscience 16: 201-209. Rodent tuber plant (Typhonium flagelliforme (G.Lodd.) Blume) contains several anticancer compounds. Mutant plants have a higher cytotoxic effect than wild-type plants. This study aimed to devise a tetra-primer ARMS PCR using lectin gene SNPs to differentiate T. flagelliforme mutants and wild-type of Bogor accessions. A protein modeling study was also conducted to investigate the impact of point mutations on the structure of protein. The tetra-primer ARMS design and in silico protein modeling analysis were based on mutation points from previously sequenced lectin genes. A pair of primers was successfully designed using the missense mutation type specific to the SNP site that causes amino acid variation. The ARMS lec183 tetra-primer focuses on a 183 bp mutation in the lectin gene that converts threonine to arginine to provide a successful lec183 primer. The ARMS lec183 primer pair did not differentiate T. flagelliforme mutant plants from wild-type of Bogor accessions. The tetra-primer ARMS lec183 could be amplified successfully in all T. flagelliforme samples at a size of 278 bp outer primer and 193 bp inner primer, as determined by primer size. In the mutant protein structure, the 183 bp mutation results in amino acid changes that closely match those in wild-type proteins.